2023
DOI: 10.1021/acsphyschemau.3c00031
|View full text |Cite
|
Sign up to set email alerts
|

Mastering Femtosecond Stimulated Raman Spectroscopy: A Practical Guide

Pauline G. Lynch,
Aritra Das,
Shahzad Alam
et al.

Abstract: Femtosecond stimulated Raman spectroscopy (FSRS) is a powerful nonlinear spectroscopic technique that probes changes in molecular and material structure with high temporal and spectral resolution. With proper spectral interpretation, this is equivalent to mapping out reactive pathways on highly anharmonic excited-state potential energy surfaces with femtosecond to picosecond time resolution. FSRS has been used to examine structural dynamics in a wide range of samples, including photoactive proteins, photovolta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 138 publications
(264 reference statements)
0
2
0
Order By: Relevance
“…10 cm –1 ) “Raman pump” pulse. The probe pulse combination generates an instantaneous stimulated Raman spectrum, which has the spectral resolution of the Raman pulse and the temporal resolution of the continuum, which is then measured as a function of pump–probe delay. The measured signal comprises a number of contributions, which must be carefully measured and separated, and the final spectrum can be complicated by interference with competing signals. , These effects are now quite well understood and can be removed or corrected for as described in detail elsewhere, although this complexity is undoubtedly a limitation of the method. , An advantage of FSRS is that the Raman pulse can be tuned into resonance with a specific transient absorption and the resonance enhancement used to extract state specific transient Raman spectra. , It should be noted that there is a Fourier transform time domain analogue of FSRS, impulsive SRS, which has fewer and simpler background correction problems and can provide outstanding signal-to-noise, but which places high demands on the laser source and experimenter, requiring sub 10 fs pulses, high stability, and long measurement times …”
Section: Methodsmentioning
confidence: 99%
“…10 cm –1 ) “Raman pump” pulse. The probe pulse combination generates an instantaneous stimulated Raman spectrum, which has the spectral resolution of the Raman pulse and the temporal resolution of the continuum, which is then measured as a function of pump–probe delay. The measured signal comprises a number of contributions, which must be carefully measured and separated, and the final spectrum can be complicated by interference with competing signals. , These effects are now quite well understood and can be removed or corrected for as described in detail elsewhere, although this complexity is undoubtedly a limitation of the method. , An advantage of FSRS is that the Raman pulse can be tuned into resonance with a specific transient absorption and the resonance enhancement used to extract state specific transient Raman spectra. , It should be noted that there is a Fourier transform time domain analogue of FSRS, impulsive SRS, which has fewer and simpler background correction problems and can provide outstanding signal-to-noise, but which places high demands on the laser source and experimenter, requiring sub 10 fs pulses, high stability, and long measurement times …”
Section: Methodsmentioning
confidence: 99%
“…The photoisomerization of stilbene has also been investigated and the structural changes have been revealed by the gradual shift of the torsional mode [18]. Moreover, the twodimensional FSRS has been recently constructed and applied to study the anharmonicity of the vibrational coherence of charge-transfer modes of an artificial dimer system [19][20][21]. In addition, the ultrafast electron pulses have been employed to study the isomerization process, and the gradual changes in structures has been shown when a wave packet passes through the CI [22].…”
Section: Introductionmentioning
confidence: 99%